Communication ethics: Principle and practice - Beckett, Robert (Journal of Communication Management, 2004)
Communication ethics, this paper argues, is a discipline ready for application to communication management and is particularly relevant as we enter an “age of information”. With a moral foundation firmly set in the social and human sciences, communication ethics offers managers a means to face unpredictable futures with greater certainty and purpose. This paper outlines an approach in which all decision making and its communication are understood as having an ethical grounding. Such an application empowers managers to act with integrity across the spectrum of their varied communication roles: through management and internal communications, public affairs and marketing; in advertising, media and publishing, and in the use of information technology. Positioned independently from the professional bodies of communication, an interdisciplinary ethics offers practitioners skills and moral frameworks that can be shared across professions and used to compare and evaluate their practice. This paper concludes by presenting a model of communication ethics that individual managers can use to prescribe a more sensitive and dynamic human‐ethical environment.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTEwOC8xMzYzMjU0MDQxMDgwNzUzOA